Retracted: Stress corrosion cracking of high strength stainless steels for use as strand in prestressed marine environment concrete construction. Issue 8 (August 2016) - Fernandez, J.
Abstract : The above article, published online on 10 April 2015 in Wiley Online Library (wileyonlinelibrary.com ), and in volume 66, pp. 1269–1278, has been retracted by agreement between the authors, the journal Editors in Chief, Jürgen Mietz, and Wiley‐VCH Verlag GmbH & Co. KGaA. The retraction has been agreed due to substantial overlap with a previously published paper, and without consultation of the co‐authors of that publication: 'Investigation of Stress Corrosion Cracking Susceptibility of High Strength Stainless Steels for Use as Strand Material in Prestressed Concrete Construction in a Marine Environment', J. Fernandez, A. A. Sagüés and G. Mullins, Paper No.2686, 15 pp., Corrosion 2013, NACE International, Houston, 2013. References Fernandez, J. (2015), Stress corrosion cracking of high strength stainless steels for use as strand in prestressed marine environment concrete construction. Materials andCorrosion, 66: 1269–1278. doi:10.1002/maco.201408190